Effects of Early Alcohol Exposure on Functional Organization and Microstructure of a Visual‐Tactile Integrative Circuit. (9th March 2018) - Tang, Shiyu; Xu, Su; Gullapalli, Rao P.; Medina, Alexandre E.
Abstract : Background: Children with fetal alcohol spectrum disorders (FASD) often have deficits associated with multisensory processing. Because ethanol (EtOH) disrupts activity‐dependent neuronal plasticity, a process that is essential for refining connections during cortical development, we hypothesize that early alcohol exposure results in alterations in multisensory cortical networks, which could explain the multisensory processing deficits seen in FASD. Here, we use a gyrencephalic animal model to test the prediction that early alcohol exposure alters the functional connectivity and microstructural features of the rostral posterior parietal cortex (PPr), a visual‐tactile integrative area. Methods: Ferrets were exposed to moderate doses of EtOH during the brain growth spurt period. Functional connectivity and microstructural features were assessed using resting‐state functional magnetic resonance imaging and ex vivo diffusion kurtosis imaging (DKI), respectively, when the animals reached juvenile age and adulthood, respectively. Results: While the whole brain volume was smaller in alcohol‐treated animals, the relative size of the frontal brain area was larger when compared to control animals. Altered functional connectivity was observed in alcohol‐treated animals, where increased connectivity was observed between PPr and the region that provides its major visual inputs (the caudal portion of the parietal cortex), but not with the region that provides its major somatosensory inputs (tertiary somatosensory cortex). DKI revealed reduced microstructural tissue complexity in all investigated sensory areas of alcohol‐treated animals. Conclusions: In this study, we observed alterations in cortical functional connectivity and microstructural integrity in a cortical area involved in multisensory processing in a ferret FASD model. These findings indicate an alteration in cortical networks that may be related to the multisensory processing deficiencies observed in FASD.